Husbandry and breeding of Greater green leafbird Chloropsis sonnerati at Jurong Bird Park, Singapore. Issue 1 (19th April 2018) - Kumar, M.; Lee, J.; Cabana, F.
Abstract : The only chloropseids known that are alive today, are the leafbirds. The Greater green leafbird Chloropsis sonnerati is a small‐sized, South East Asian passerine that is being threatened by the songbird trade. At Jurong Bird Park, Singapore, C. sonnerati bred for the first time in January 2017. This article will describe the methods utilized to breed this species successfully, including using a bamboo‐fibre canary nest. Initial observations of nesting Greater green leafbirds in a mixed aviary showed that C. sonnerati were consistently disturbed by the pair of Red crested turaco Tauraco erythrolophus . The turacos were removed from the aviary and this allowed the Greater green leafbirds to build a nest and lay two eggs. Chloropsis sonnerati incubated the eggs for 14 days and the first egg hatched on 1 January 2017. Parents were observed taking good care of the chicks for the first 6 days but one chick was found dead on the ground on day 7. The remaining chick was transferred to the Breeding & Research Centre (BRC) to be hand reared. The C. sonnerati juvenile was observed perching on the nest basket on day 16 and it fledged on day 34. We attribute this successful leafbird breeding to the type of nest, nesting materials, diet and hand‐rearing diet, and the detailed observations and care by the keepers. Abstract : The Greater green leafbird Chloropsis sonnerati is a small‐sized, South East Asian passerine that is being threatened by the songbird trade. At Jurong Bird Park, Singapore, C. sonnerati bred for the first time in January 2017. This article describes the special methods put in place in order to breed this species successfully, including the provision of a lined bamboo‐fibre nest, adjustments to the aviary‐management and husbandry routine, and dietary modifications. Two chicks hatched and one was hand reared to independence. (Photo: Manoj Kumar, Wildlife Reserves Singapore)